Branding South Korea in a Competitive World Order: Discourses and Dispositives in Neoliberal Governmentality - Schwak, Juliette (Asian studies review, 2016)
Since 2008, the South Korean administration has invested significant budgetary and political resources in its nation branding strategy, involving the private sector and Korean citizens in this endeavour. This article takes Korea as an exemplary case study of the way many states have enrolled their citizens, through nation branding, in the construction of a collective competitive identity. This study is based on an empirically deductive methodology, looking at the industry literature on nation branding, official sources, iconography and videos from the Korean nation branding campaign, and drawing on interviews with actors and observers of this campaign. I suggest that Korean nation branding should be seen as a continuation of the capitalist developmental project initiated by Park Chung-Hee in 1960s. Lee Myung-Bak's nation branding campaign belongs to a series of strategies aiming at transforming South Korean into a successful global site of capitalist accumulation. This path dependency involves citizen mobilisation, and this is analysed through a Foucauldian prism: this article shows that although modalities of social control have evolved with the democratisation in 1987, they still play a role, combining coercion and non-coercive technologies of the self, in seeking to transform Korean citizens into competitive capitalist subjects.